Factors influencing the anti-impact performance of a “roadway rock support” system - Tang, Zhi; Zuo, Wenbo; Gao, Ke; Cai, Xiaoqiao (Frontiers in Earth Science, 2023)
To improve the impact protection performance of the ' roadway rock-support' system and provide a theoretical basis for the design of coal mine impact ground pressure roadway support. The mechanical model of the tunnel roadway of the circular section considering damage is established. According to the instability theory of rock burst disturbance response, the formula of critical rock burst load of circular roadway is derived. The influence of mechanical properties of surrounding rock and roadway support strength on critical rock burst load of ' roadway rock-support' system is studied by using the control variable method. The research shows that: (1) Under the support condition of roadway, with the increase of uniaxial compressive strength, softening modulus and internal friction angle of surrounding rock, the critical rock burst load of roadway has an increasing trend; the critical rock burst load of roadway decreases with the increase of elastic modulus of surrounding rock. (2) Under the condition of no support, with the increase of uniaxial compressive strength, elastic modulus and internal friction angle of surrounding rock, the critical rock burst load of roadway tends to increase. With the decrease of surrounding rock softening modulus, the critical rock burst load of roadway decreases. When the above four kinds of surrounding rock influence factors are the same, the critical load of rock burst under supporting condition is much larger than that under non-supporting condition. (3) A new impact tendency index K is defined as the ratio of softening modulus and elastic modulus. (4) The critical load of rock burst increases approximately linearly with the increase of support stress. The critical load of rock burst is about 400 times in the supporting stress. Increasing roadway support strength can greatly improve the stability of supporting and roadway surrounding rock system, and the stability of supporting and roadway surrounding rock system can be improved by reasonably changing the mechanical properties of surrounding rock.